Evaluation of the analgesic activity and safety of ketorolac in whole body fractionated gamma irradiated animals - Sara Aly; Mona F. Mahmoud; Seham H.M. Hassan; Ahmed Fahmy (SpringerOpen, 2015)
This study was performed to evaluate the analgesic activity and the toxicity of ketorolac in normal and fractionated (1.5 Gy/day/4 days) γ-irradiated animals. Determination of brain serotonin content and serum prostaglandin level were also undertaken. The analgesic activity was tested using formalin test, at three dose levels (15, 30 and 60 mg/kg) after 1 and 7 days post radiation exposure. LD50 determinations and assessment of liver and kidney function tests were performed. Our results indicated marked analgesic effects on the early and late phases of nociception. Double treatment with ketorolac and irradiation increased brain serotonin content. The acute LD50 of ketorolac was decreased in irradiated animals as compared to the LD50 of normal animals. Double treatment with ketorolac and irradiation induced an elevation of gastric mucin content, urea and BUN levels on the 1st day post irradiation, whereas, albumin level was lowered and globulin level was elevated after 7 days post irradiation. Depending on this study the dose of ketorolac used for treating cancer patients addressed to radiotherapy should be reduced, however, this requires further clinical confirmation.